2021
DOI: 10.1177/17448069211066221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting spinal secretory phospholipase A2 after painful nerve root injury attenuates established pain and spinal neuronal hyperexcitability by altering spinal glutamatergic signaling

Abstract: Neuropathic injury is accompanied by chronic inflammation contributing to the onset and maintenance of pain after an initial insult. In addition to their roles in promoting immune cell activation, inflammatory mediators like secretory phospholipase A2 (sPLA2) modulate nociceptive and excitatory neuronal signaling during the initiation of pain through hydrolytic activity. Despite having a known role in glial activation and cytokine release, it is unknown if sPLA2 contributes to the maintenance of painful neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Nerve injury is accompanied by chronic inflammation, leading to the generation and maintenance of neuropathic pain. Inflammatory mediators such as secreted phospholipase A2 (sPLA2) regulate nociceptive and excitatory neuronal signaling during the development of pain through hydrolytic activity (Kartha et al, 2021). In the chemotherapy pain model, it was demonstrated that the pro-inflammatory mediators in the dorsal root ganglion (DRG) increased, indicating the induction of neuroinflammation in DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve injury is accompanied by chronic inflammation, leading to the generation and maintenance of neuropathic pain. Inflammatory mediators such as secreted phospholipase A2 (sPLA2) regulate nociceptive and excitatory neuronal signaling during the development of pain through hydrolytic activity (Kartha et al, 2021). In the chemotherapy pain model, it was demonstrated that the pro-inflammatory mediators in the dorsal root ganglion (DRG) increased, indicating the induction of neuroinflammation in DRG.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PLA2 in maintaining pain and central neural sensitization after neural injury has been demonstrated. Inhibiting spinal PLA2 during painful injury reduced neuronal firing in the spinal cord and elevates intracellular glutamate concentration; thus, suggesting that spinal PLA2 is implicated in spinal mechanisms of neuronal excitability via glutamate signaling, neurotransmitters, or inflammatory cascades ( Quindlen-Hotek et al, 2020 ; Kartha et al, 2021 ). Although the exact mechanism via which PLA2 cause peripheral and central itch sensitization is not well understood, we propose that its ability to stimulate signal transduction and excitation of itch sensory neurons may contribute to peripheral sensitization.…”
Section: Peripheral Neural Sensitization In Chronic Itchmentioning
confidence: 99%
“…Intrathecal treatment with antisense oligodeoxynucleotide or siRNA targeting sPLA2-III was able to reverse established thermal hyperalgesia. Using a well-established model of pain associated with nerve root compression, Kartha et al 45 investigated how sPLA2 in the spinal cord mediates the process of maintaining pain after nerve injury. The results showed that the level of sPLA2 was upregulated within 4 hours in spinal cord injury, and immediate inhibition could prevent the occurrence of pain and spinal cord hyperexcitability.…”
Section: Recent Progress Of Nanomedicine Targeting Spla2 In the Treat...mentioning
confidence: 99%